(untitled) (International relations and international law Journal, 2016)
The article is devouted to the emergence of reasons and prerequisites of the DPRK’s nuclear program.From middle of the XX century the Korean peninsula is the territory of the conflict and a zone of escalation of the relations in AsiaPacific region. Certainly, precedent of current situation was the Korean war of 1950-1953, which led subsequently to final split of once uniform country on two competing states. Political, economical, ideological fight between USSR and USA after war in Korea, when they were separated is written in the work. Besides, the major factor attracting attention of the international community to the situation on the Korean peninsula is the nuclear program of North Korea, served as the reason of numerous nuclear crises, and playing role of destabilizing factor of securitysystem inAsia-Pacific region throughout long time